Impact Of Scheduling Drugs Under The 1971 Convention On Psychotropic Substances A Follow-Up Study* - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1983)

(untitled)
It will be recalled that at the 1982 Seventh Special Session the Commission on Narcotic Drugs adopted a Resolution 2 (S-VII) on Procedures to be followed by the Commission in matters of scheduling narcotic drugs and psychotropic substances. As part of that resolution; the" Commission requested member states for "information on the economic, social," legal and administrative factors related to the abuse of substances being considered for possible scheduling and to supply as completed data as possible on any illicit trafficking in the substances in question" . In response to the above resolution an Impact Study was carried out with the objectives of developing and applying a data gathering methodology so as to obtain and assess relevant information on substances being considered for control which the Commission might usefully consider. This study was reported at the 30th Regular Session of UNCND held in Vienna in February 1983 entitled "Impact of Scheduling Drugs Under the 1971 Convention on Psychotropic Substances - The Benzodiazepines Reappraised".